MENURUNKAN KERUSAKAN YANG TIDAK TERJADWAL (UNSCHEDULE BREAKDOWN) SISTEM BAHAN BAKAR PADA UNIT KOMATSU HD 1500-7 DIPT UT SITE KALIMANTAN TIMUR - Vuko A.T. Manurung; Yohanes Trijoko; Randy Putra Afani (President University, 2019)
This study discusses the modification of the fuel system in the Komatsu HD 1500-7 unit, which aims to improve PA (physical avaibility) and make unit downtime faster. The basis of this research was carried out because of the frequent replacement of fuel filters due to clogged fuel flow so that the cost of repairs and the consequences of not operating the unit became high. This repair process uses the main components in the form of Arduino Mega 2560 program, LED lights, LCD monitors and sensors. The working principle of this improvement is that the tool works together to forward the voltage signal from the sensor to Arduino, then the signal will be converted into writing data on the LCD. The LED light functions as a warning lamp and the speaker in the cabin functions as a warning sound. The result of making this modification system is that it can be determined the right time to replace the fuel filter before a deadlock occurs and cause the unit to die suddenly.Keywords. fuel system, Physical Avaibility, Downtime